Assessment of motor function for upper and lower extremities among patients with chronic stroke (Latakia University Journal -Medical Sciences Series, 2024)
Assessment of motor function is essential for the effective management of chronic stroke patients, as it provides valuable information about the patient’s functional ability, diagnosis, and treatment effectiveness. Therefore, the current study aimed to assess motor function in 45 chronic stroke patients who were selected using a convenience sample method from the Department of Physical Therapy at Tishreen University Hospital   in Lattakia. Data were collected using research tools. The results showed that the majority of patients had significant motor weakness with regard to the gross motor function of the upper and lower extremities. The study recommended finding a comprehensive protocol for evaluation, developing new techniques, conducting research on evaluation obstacles, and emphasizing the integration of regular evaluations of motor function into the practices of Health care professionals.